(untitled) (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1973)
The AA. observed the pattern of the ansa spiralis in giraffe. The ansa spiralis had a irregular arrangement: it was seen with three centripetal and three anda half centrifugal coils.